Investigation on unfrozen water content models of freezing soils - Bi, Jun; Wang, Guoxu; Wu, Zhijian; Wen, Haiyan; Zhang, Yingmin; Lin, Gaochao; Sun, Tian (Frontiers in Earth Science, 2023)
Unfrozen water content is a significant hydro-thermal property in numerical modeling in cold regions. Although numerous models have been developed to mimic the variation of unfrozen water content with subzero temperature, comprehensive evaluation of unfrozen water content models is scarce. This study collected a total of 29 models and divided them into four categories, namely, theoretical models, soil water characteristic curve (SWCC)-based models, empirical models, and estimation models. These models were evaluated with 1278 experimental points from 16 studies covering multiple soil types, including 24 clays, 18 silty clays, 7 silts, 19 sands, and 10 sandstones. Root mean square error (RMSE) and average deviations (AD) were applied to judge the performance of these models. Most unfrozen water content models can well simulate the relationship between unfrozen water content and subzero temperature. Among the aforementioned four categories of unfrozen water content models, Lizhm et al. model, Fredlund and Xing(C=1)-Wen model, Kozlowski empirical model, and Kozlowski estimation model performed best in their respective categories. Compared to the rest three categories, estimation models can be applied to predict the variation of unfrozen water content with subzero temperature by some easy-to-obtain soil physical parameters and provide guidance for the development of unfrozen water content models.